Soft-sediment deformation structures in seismically affected deep-sea Miocene turbidites (Cilento Basin, southern Italy) - Valente, Alessio; Ślączka, Andrzej; Cavuoto, Giuseppe (Bogucki Wydawnictwo Naukowe, 2014)
Soft-sediment deformation structures (SSDS) are widespread in the upper part of the S. Mauro Formation (Cilento Group, Middle-Late Miocene). The succession is represented mainly by thick and very thick, massive, coarse-grained sandstones, deposited by rapid sedimentation of high-density turbidity currents. The most common SSDS are short pillars, dishes, sedimentary sills and convolutions. They occur mostly in the upper parts of sandstone beds. Vertical tubes of 4–5 cm in diameter and up to 50 cm long constitute the most striking structures. They begin in the middle part of sandstone beds, which are basically massive or contain faint dish structures. These tubes can bifurcate upwards and/ or pass into bedding-parallel veins or dikes. The vertical tubes sometimes form sand volcanoes on the then sedimentary surface. The SSDS are interpreted as the result of earthquake-triggered liquefaction and/or fluidisation of the turbidites that were affected by the seismic shocks. This implies that the deformed layers should be considered as seismites.
Keywords: High-density turbidites; Soft-sediment deformation structures; Seismites; Apennines; Cilento Group; Miocene; Italy